2009
DOI: 10.1089/end.2008.0506
|View full text |Cite
|
Sign up to set email alerts
|

Management of Colon Injury After Percutaneous Renal Surgery

Abstract: Percutaneous access to the kidney has gained widespread use during the last decades. Iatrogenic colon injury is an uncommon but serious complication. Diagnosis is sometimes delayed, and treatment strategies are still controversial, including conservative management, colostomy, or primary repair. The aim of this review is to identify optimal diagnostic and treatment options for such injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…According to a review of the literature, 24.1 % of the patients were diagnosed intraoperatively, whereas 75.9 % of the patients were diagnosed in the postoperative period (mean 2.9 days) [16]. In our study, 31.8 % of the patients were diagnosed during the PNL procedure, whereas 68.2 % of the patients were diagnosed after the operation.…”
Section: Discussionmentioning
confidence: 42%
“…According to a review of the literature, 24.1 % of the patients were diagnosed intraoperatively, whereas 75.9 % of the patients were diagnosed in the postoperative period (mean 2.9 days) [16]. In our study, 31.8 % of the patients were diagnosed during the PNL procedure, whereas 68.2 % of the patients were diagnosed after the operation.…”
Section: Discussionmentioning
confidence: 42%
“…27,30 Our patient's benign clinical appearance, with a chief complaint of sore throat and without fever, leukocytosis, leukopenia, abdominal pain, or other clinical evidence of peritonitis, belied the peritoneal involvement seen on imaging and the bowel wall defect with fecal spillage seen laparoscopically. With recognition of the injury, despite its unusual presentation, and prompt operative management, the patient achieved a relatively rapid and uncomplicated recovery.…”
Section: Resultsmentioning
confidence: 80%
“…Korkes et al, advocated the colonic tube to be removed when intestinal and urinary tract diversion have been proven. (21) Zuckerman and Desai reported that if in the postoperative period, fecal material in the nephrostomy tube, blood in the feces, pneumaturia, nausea, ileus, vomiting, leukocytosis, fever, sepsis or peritonitis is noted then it should be associated with bowel injury. (22) In the case of extraperitoneal injuries, conservative management may be preferred.…”
Section: Resultsmentioning
confidence: 99%